2013
DOI: 10.1073/pnas.1311592111
|View full text |Cite
|
Sign up to set email alerts
|

The antigen 43 structure reveals a molecular Velcro-like mechanism of autotransporter-mediated bacterial clumping

Abstract: Aggregation and biofilm formation are critical mechanisms for bacterial resistance to host immune factors and antibiotics. Autotransporter (AT) proteins, which represent the largest group of outer-membrane and secreted proteins in Gram-negative bacteria, contribute significantly to these phenotypes. Despite their abundance and role in bacterial pathogenesis, most AT proteins have not been structurally characterized, and there is a paucity of detailed information with regard to their mode of action. Here we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
197
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(211 citation statements)
references
References 50 publications
12
197
0
2
Order By: Relevance
“…Ag43 is composed of two domains: the ␤ domain, which forms an outer membrane integrated pore, and the ␣ domain, which is secreted to the extracellular environment through the folded ␤ domain after processing of the Ag43 preprotein. The ␣ and ␤ domains remain in contact via noncovalent interactions (70). Ag43␣ promotes bacterial autoaggregation and biofilm formation, and it adopts a parallel right-handed ␤-helix conformation that resembles the amyloid structure established for curli (Fig.…”
Section: Surface-associated Proteins With Amyloidogenic Propertiesmentioning
confidence: 95%
See 1 more Smart Citation
“…Ag43 is composed of two domains: the ␤ domain, which forms an outer membrane integrated pore, and the ␣ domain, which is secreted to the extracellular environment through the folded ␤ domain after processing of the Ag43 preprotein. The ␣ and ␤ domains remain in contact via noncovalent interactions (70). Ag43␣ promotes bacterial autoaggregation and biofilm formation, and it adopts a parallel right-handed ␤-helix conformation that resembles the amyloid structure established for curli (Fig.…”
Section: Surface-associated Proteins With Amyloidogenic Propertiesmentioning
confidence: 95%
“…However, this structure cannot be considered a typical amyloid fibril because the protein remains anchored to the cell surface and is unable to polymerize into fibers. In addition, it was described that pairs of ␣ domains mediate interaction between different cells through a "Velcro-like" mechanism in which the formation of ␣ homodimers organized in a head-to-tail conformation and stabilized by hydrogen bonds and electrostatic interactions results in the aggregation of cells (70).…”
Section: Surface-associated Proteins With Amyloidogenic Propertiesmentioning
confidence: 99%
“…By swapping portions of autoaggregating alleles with non-aggregating ones, Klemm et al (2004) found that the autoaggregating phenotype of the Agn43 protein is conferred by residues in the first 160 amino acids of its externally-exposed 499-residue passenger domain. Heras et al (2014) subsequently showed that a head-to-tail Velcro-like interaction between the inner long arm and the outer edge, of what they discovered to be Lshaped passenger domains of antigen 43 on adjacent cells, is the molecular explanation for autoagregation (Heras et al, 2014). When Meng et al (2011) solved the structure of the passenger domain of Haemophilus influenzae SAAT, they revealed it to be a prism produced from a b-strand coil with three b-strand faces.…”
Section: Discussionmentioning
confidence: 99%
“…Ag43a has been shown to be the principal AT contributing to CFT073 colonisation in the mouse bladder (Ulett et al, 2007b). Recent crystallography data obtained from the purified Ag43 passenger domain revealed it to possess an L-shaped tertiary structure, which perpendicularly dimerises in a velcro-like manner with an Ag43 protein from another cell (Heras et al, 2014 Upon translocation across the OM, SPATE proteins are autoproteolytically cleaved in between two conserved asparagine residues (FxxEVNNLNK motif) within the α-helix linker region . Cleavage occurs inside of the β-barrel pore, releasing the SPATE protein in the extracellular milieu.…”
Section: Type V Secretion Pathwaymentioning
confidence: 99%
“…However, this phenotype was not examined further. Ag43 is phase variable AIDA-I type AT protein characterised by the ability to bind to independent Ag43 molecules expressed on neighbouring cells (Heras et al, 2014). This…”
Section: Growth Characteristics Of Mg1655 Periplasmic Chaperone Mutanmentioning
confidence: 99%